KORELASI SELF DIRECTED LEARNING DENGAN HASIL BELAJAR KOGNITIF IPA PADA MASA PANDEMI COVID-19 KELAS VIII SMP N 23 PEKANBARU - Dewi Irma Hastuti; Wan Syafi’i; Riki Apriyandi Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to determine the correlation between self-directed learning and science cognitive learning outcomes during the Covid-19 pandemic for class VIII SMP N 23 Pekanbaru. In order to achieve this goal, quantitative research was carried out in the form of correlation research and descriptive research design. The variables observed in this study were self-directed learning and students' science cognitive learning outcomes which were carried out in November 2021 - January 2022. The instruments used were validation sheets, self-directed learning questionnaires and test instruments. The data sources come from primary data, namely the results of closed questionnaire data from self-directed learning and the results of students' cognitive tests in the form of objective questions on the natural sciences material of motion systems in living things and open interviews. The results of the study showed that there was a significant correlation between self-directed learning (X) and science cognitive learning outcomes (Y) in the moderate category in science learning class VIII SMP Negeri 23 Pekanbaru during the Covid-19 pandemic in the 2021/2022 academic year. Self-directed learning affects cognitive science learning outcomes by 17.93% and the remaining 82.1% is influenced by other factors not determined in this study. So based on the results of this study it would be very good if students were able to improve self-directed learning to support improving their learning outcomes.Key Words: Self Directed Learning; Science Cognitive Learning Outcomes; Covid-19 pandemic